The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.26502/jsr.10020209
|View full text |Cite
|
Sign up to set email alerts
|

Post-Operative Atrial Fibrillation: Current Treatments and Etiologies for a Persistent Surgical Complication

Abstract: Post-operative atrial fibrillation (POAF) is a persistent and serious surgical complication that occur in 20-55% of cardiac surgery cases. POAF may lead to adverse health outcomes such as stroke, thromboembolism, cardiac arrest, and mortality, and may develop long-term. Patients have a 2-fold increase in mortality risk and spend about 3.7 more days in the hospital and $16,000 more in medical costs during their visit. The mechanisms and risk factors of POAF are still poorly understood, yet a strong foundation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 64 publications
1
26
2
2
Order By: Relevance
“…In addition, electrolyte disturbances in the postoperative period can also play a role in the pathogenesis of postoperative atrial fibrillation. Some of the risk factors for postoperative atrial fibrillation include advanced age, male gender, white race, and the presence of comorbidities such as chronic obstructive pulmonary disease, congestive heart failure, hypertension, prior history of atrial fibrillation, diabetes mellitus, hyperthyroidism, chronic kidney disease, obesity, and echocardiographic evidence of left atrial enlargement and left ventricular dysfunction [3,12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, electrolyte disturbances in the postoperative period can also play a role in the pathogenesis of postoperative atrial fibrillation. Some of the risk factors for postoperative atrial fibrillation include advanced age, male gender, white race, and the presence of comorbidities such as chronic obstructive pulmonary disease, congestive heart failure, hypertension, prior history of atrial fibrillation, diabetes mellitus, hyperthyroidism, chronic kidney disease, obesity, and echocardiographic evidence of left atrial enlargement and left ventricular dysfunction [3,12].…”
Section: Discussionmentioning
confidence: 99%
“…While it has been suggested that vitamin D deficiency may be a risk factor for postoperative atrial fibrillation as it plays a role in reducing inflammation and acts as a negative regulator of RAAS and in improving overall cardiovascular health, some of the prior studies failed to demonstrate a significant correlation between low levels of vitamin D and the occurrence of new or postoperative atrial fibrillation conclusively [3,4]. Our review analyzed three randomized controlled studies in which people with vitamin D deficiency were given vitamin D supplementation in the preoperative period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…New-onset POAF can be a marker of increased illness severity. 43 , 44 However, early identification of high-risk patients can lead to initiating preventive measures (eg, utilizing drugs such as beta-blockers, statins, oral anticoagulants, antiarrhythmics, and electrolyte supplementation 45 ) before adverse cardiac events to reduce mortality and improve clinical outcomes. Prophylactic amiodarone used in high-risk individuals effectively reduced the incidence of POAF, improved outcomes, and reduced the associated health resource utilization and costs.…”
Section: Discussionmentioning
confidence: 99%
“…Das postoperative Vorhofflimmern (POAF) ist eine häufige und unterschätzte Komplikation, die nach herzchirurgischen Eingriffen in 20-55 % der Fälle auftritt. POAF führt zu längerer Krankenhausverweildauer, erhöhter Morbidität und Letalität beispielsweise durch das Auftreten von Schlaganfällen, Thrombembolien, Herzstillstand und Übergang in chronisches Vorhofflimmern und verursacht somit deutlich erhöhte Kosten im Gesundheitswesen [20]. Im Folgenden werden Strategien zur Prophylaxe und Therapie des POAF vorgestellt.…”
Section: Postoperatives Vorhofflimmern (Poaf) In Der Herzchirurgieunclassified